Analisis Kebisingan dan Getaran pada Kamar Mesin Kapal: Noise and Vibration Analysis in Ship Engine Rooms - Candra Am'isa, Johanes (Blueprint Journal, 2025)
Noise and vibration occurring in the ship's engine room can significantly impact the crew's health and the passengers' comfort. This study aims to analyze the level of noise and vibration on a research vessel powered by an electric motor. The method used includes measuring noise and vibration with specialized tools to evaluate the impact on health. The results show that the average noise level reaches 102.7 dB, exceeding the established threshold of 85 dB. Therefore, using ear protection devices (APD) is highly recommended to reduce health risks. Although the noise on the vessel does not necessarily make it unpopular, it is essential to further investigate the impact of noise and vibration felt by engine operators over a long period, as it can affect their health. This research is necessary to minimize the noise level on ships through understanding the characteristics of noise itself. Excessive noise levels can have serious negative impacts, both in terms of health, psychological, and technical aspects.